Evaluation Of Antibacterial Activity In Pelargonium Graveolens Extracts - Pedraza, Paula Sofía Rojas; Aguirre , Oscar Eduardo Rodriguez; Palacios, Janeth del Carmen Arias (International Journal of Membrane Science and Technology, 2023)
The antibacterial activity of the total ethanolic extract and fractions of Pelargonium graveolens against Candida albicans, Escherichia coli, Pseudomonas spp, Staphylococcus aureus and Bacillus spp. Methods: To measure the relative antimicrobial activity, the percentage of inhibition was calculated by the plate and well method. Results: It was established that the highest antimicrobial activity was presented by the oily extract without preference for Gram positive or Gram negative, the acetone fraction with a value of 58.53% inhibition. The hexane fraction has activity greater than 100% only against S. aureus. Conclusions: The extracts of P. graveolens present antimicrobial activity against Gram-positive and Gram-negative bacteria and yeasts, especially the oily extract, which presented the highest percentage of inhibition recorded against Escherichia coli, Staphylococcus aureus and Candida albicans, respectively; while for Pseudomonas aeruginosa and Bacillus subtilis, the extract that presented the highest percentage of inhibition was ethyl acetate.